Impact of maternal BMI and sampling strategy on the concentration of leptin, insulin, ghrelin and resistin in breast milk across a single feed: a longitudinal cohort study - Andreas,NJ; Hyde,M; Herbert,B; Jeffries,S; Santhakumaran,S; Mandalia,S; Holmes,E; Modi,N (BMJ Open, 2016)
Objectives: We tested the hypothesis that there is a positive association between maternal BMI and the concentration of appetite-regulating hormones leptin, insulin, ghrelin and resistin in breast milk. We also aimed to describe the change in breast milk hormone concentration within each feed, and over time.Setting: Mothers were recruited from the post-partum ward at a university hospital in London. Breast milk samples were collected in the participants homes.Participants: We recruited 120 healthy, primiparous, breastfeeding mothers, over 18 years old. Mothers who smoked, had multiple births, or had diabetes were excluded. Fore and hind milk samples were collected from 105 women at one week post-partum and 92 women at three months post-partum. Primary and secondary outcome measures: We recorded maternal and infant anthropometric measurements at each sample collection and measured hormone concentrations using a multiplex assay.Results: The concentration of leptin in fore milk correlated with maternal BMI at time of sample collection, at seven days (r=0.31, p=0.02), and three months post-partum (r=0.30, p=<0.00). Fore milk insulin correlated with maternal BMI at three months post-partum (r=0.22, p=0.04). Breast milk ghrelin and resistin were not correlated with maternal BMI. Ghrelin concentrations at three months post-partum were increased in fore milk compared to hind milk (p=0.01). Concentrations of ghrelin were increased in hind milk collected at one week post-partum compared to samples collected at three months post-partum (p=0.03). A trend toward decreased insulin concentrations in hind milk was noted. Concentrations of leptin and resistin were not seen to alter over a feed.